Single Parents' Subjective Wellbeing over the Welfare to Work Transition - Cook, K (My University, 2012)
The Australian government purports that employment will improve welfare recipients' wellbeing. However, longitudinal analysis of the subjective wellbeing (SWB) of 135 single parents who were compelled to make the transition from welfare to work revealed that as work hours increased, subjective wellbeing did not improve, and in some cases worsened. Participants who were employed at baseline increased their work hours by an average of 4.75 hours per week; however no change was detected in their SWB. Conversely, participants who moved from not working at baseline to working at follow-up increased their work hours by an average of 15.84 hours per week. For these participants, the change in work hours negatively predicted 20–34 per cent of the variance in SWB. From these data, it is concluded that those parents who were already working were those who faced fewer barriers to employment compared to those who were compelled to work. Those who were previously unemployed may not have the material, social and psychological resources to make a successful work transition.
Social Policy and Society
Keywords: Health&Wellbeing; Employment; Health and wellbeing; Labour market; Employment; Health&Wellbeing; Employment and unemployment; Health and wellbeing